School in the Soviet Painting of the 1950s: Pictorial Representation of Ideological Strategie - O. V. Bezzubova; P. A. Dvoinikova; A. V. Smirnov (Концепт: философия, религия, культура, 2020)
The main issue the paper concerns is the theoretical and cultural interpretation of the 1940- 1950s social realist art depicting the Soviet school. The study advocates for a closer attention of cultural studies to the intertwining phenomena of Soviet mundanity and politically-charged painting. Hypothetically, the interconnection could be attributed to the transformation of the Soviet culture as a whole, with the pedagogical model of Soviet school as one key institutional elements. As Soviet art represented the state political project, each topic and body served some ideological needs. Thus, the paper aims at clarifying the cultural functions school art played. The analysis is dedicated to the post-WW2 canvases, to the period of the late 1940s‒1950s in particular due to the basic shifts in socialist realist painting both in terms of form and essence, which paralleled social and political transformations. The visual studies’ approach to artistic objects adopted by the authors serves as methodological contribution to cultural studies closely connected to political history, as it highlights the ideological sources of Soviet school painting and implicit pedagogical strategies designed to implement the Soviet social policy. The article provides the examples of the most significant paintings concerning the issue. The study has revealed that the era of school art combined a significant feature of early Soviet art – monumental pathos (however, deprived of motifs connected with the Great patriotic war and the 1917 revolution) – with micro-level mundane topics, mostly labour episodes. What is particular about school as such a topic is the role this institution played in the Soviet anthropologic project. As early stages of education are proved to be the most efficient in accelerating a new type of a socialist person, a future Soviet worker, the school realm was the base of value and practices indoctrination. The state policy translated the societal needs and purposes into the art. Having examined the key ideological concepts of the Soviet culture being inherent in Soviet school painting, certain functions were discovered. School is firstly depicted just as a background of state apotheosis. Secondly, it is perceived as a sacral locus where one becomes a Soviet person is both rituals and practices. Thirdly, school art is used to explain the novel principles of constructing a new person – personal approaches combined with growing group responsibility. And, finally, all that contributes to depicting the character traits which pupils was supposed to develop at school.